Exploring metabolomic dynamics in acute stress disorder: amino acids, lipids, and carbohydrates - Gary, Nicholas C.; Misganaw, Burook; Hammamieh, Rasha; Gautam, Aarti (Frontiers in Genetics, 2024)
Acute Stress Disorder (ASD) is a psychiatric condition that can develop shortly after trauma exposure. Although molecular studies of ASD are only beginning, groups of metabolites have been found to be significantly altered with acute stress phenotypes in various pre-clinical and clinical studies. ASD implicated metabolites include amino acids (β-hydroxybutyrate, glutamate, 5-aminovalerate, kynurenine and aspartate), ketone bodies (β-hydroxybutyrate), lipids (cortisol, palmitoylethanomide, and N-palmitoyl taurine) and carbohydrates (glucose and mannose).Network and pathway analysis with the most prominent metabolites shows that Extracellular signal-regulated kinases and c-AMP response element binding (CREB) protein can be crucial players. After highlighting main recent findings on the role of metabolites in ASD, we will discuss potential future directions and challenges that need to be tackled. Overall, we aim to showcase that metabolomics present a promising opportunity to advance our understanding of ASD pathophysiology as well as the development of novel biomarkers and therapeutic targets.